The Application of Blockchain Technology-Based Accounting and Its Impact on Transparency and Financial Performance of Village-Owned Enterprises (BUMDes) in East Java - Ari Nurcahyo Darmawan; Vierly Ananta Upa (STIEKOP MALANG PRESS, 2026)
Purpose – This study aims to investigate the application of blockchain technology in the accounting systems of Village-Owned Enterprises (BUMDes) in East Java, Indonesia, and to examine its impact on financial transparency and financial performance. It also examines the mediating role of financial transparency in the relationship between blockchain technology adoption and financial performance. Design/methodology/approach – This study employed a quantitative research design. Data were collected through structured questionnaires from 150 BUMDes managers and financial officers across selected regencies in East Java, Indonesia. The data were analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS) to examine the direct effects of blockchain technology adoption on financial transparency and financial performance and the mediating effect of financial transparency. Findings – The results show that blockchain technology adoption has a significant positive effect on financial transparency (? = 0.67, p < 0.001) and financial performance (? = 0.52, p < 0.001). Furthermore, financial transparency partially mediates the relationship between blockchain adoption and financial performance. These findings indicate that blockchain adoption can improve financial outcomes not only through direct operational benefits but also by strengthening transparency and accountability in BUMDes accounting systems. Research limitations/implications – This study is limited to selected BUMDes in East Java, which may restrict the generalizability of the findings to other regions or types of village enterprises. The cross-sectional design also limits the ability to assess the long-term effects of blockchain adoption. Future research could employ longitudinal approaches and investigate additional factors such as digital literacy, organizational readiness, cybersecurity, regulatory support, and implementation costs. Originality/value – This study contributes to the literature on digital innovation and public sector accounting by integrating blockchain adoption, financial transparency, and financial performance within a single empirical framework. Its originality lies in positioning financial transparency as a mediating mechanism through which blockchain technology contributes to improved financial performance.